Differences in biocompatibility of microneedles from cyclic olefin polymers with human endothelial and epithelial skin cells. Issue 3 (19th November 2018) - Schossleitner, Klaudia; O'Mahony, Conor; Brandstätter, Stefan; Haslinger, Michael J.; Demuth, Sabrina; Fechtig, Daniel; Petzelbauer, Peter
Abstract: Microneedles are promising devices for transdermal delivery and diagnostic applications, due to their minimally invasive and painless nature of application. However, so far, applications are limited to small scale research projects. Material selection and production for larger projects remain a challenge. In vitro testing using human cell culture could bridge the gap between cost effective screening of suitable materials and concerns for safety and ethics. In this study, materials were tested for effects on viability and morphology of human endothelial cells and keratinocytes. In addition, materials were assessed for their potential to influence cellular differentiation and barrier formation. Elution‐based testing of inflammatory markers revealed no negative effects in all applied tests, whereas the assessment of differentiation markers on cells in direct contact with the material showed differences and allowed the selection of candidate materials for future medical device applications. This study illustrates that elution‐based biocompatibility testing can paint an incomplete picture. Advanced staining techniques and cell types specific for the application of the medical device improve material selection to reduce and replace animal testing at an early stage in the development process. © 2018 The Authors. journal Of Biomedical Materials Research Part A Published By Wiley Periodicals, Inc. J Biomed Mater Res Part A: 107A: 505–512, 2019.